Evaluation of Some Immunological Markers in Patients with Behcet’s Disease - Fareed Salloom, Dunya; Saad Salih, Dhuha; T. Al-Khafaji, Jasem (Iraqi Journal of Science, 2023)
The local study were selected 70 Iraqi Arab Patients (39 females and 31 males), who referred to HLA laboratory in teaching laboratories in Baghdad medical city from April 2009 – May 2010 were diagnosed with Behcete’s disease, C-reactive protein concentration(CRP) was evaluated by ELISA technique, anti-nuclear antibody (ANA) and anti-neutrophil cytoplasmic antibody (ANCA) were evaluated by Indirect immunofluorescence technology. The result showed significant differences (P<0.05) of CRP concentration in patients group compared with control, negative antinuclear nuclear antibody in all cases while ANCA was positive in 8.5% of patients with type P (PANCA). These results lead to suggest that ANCA auto-antibody may have a role in triggering BD.